Longitudinal trajectories of mental health and loneliness for Australian adolescents with‐or‐without neurodevelopmental disorders: the impact of COVID‐19 school lockdowns. (22nd February 2022) - Houghton, Stephen; Kyron, Michael; Lawrence, David; Hunter, Simon Charles; Hattie, John; Carroll, Annemaree; Zadow, Corinne; Chen, Wai
Abstract : Background: The impact of COVID‐19 (SARS‐CoV‐2) pandemic school lockdowns on the mental health problems and feelings of loneliness of adolescents with neurodevelopmental disorders (NDDs) is hypothesized to be greater than that of their non‐NDD peers. This two and a half year longitudinal study compared changes in the mental health and loneliness of Western Australian adolescents pre‐COVID‐19 (November 2018 and April 2019), immediately prior to COVID‐19 school lockdowns (March 2020), and post schools reopening (July/August 2020). Methods: An age‐and‐gender matched sample of 476 adolescents with‐or‐without NDDs completed online assessments for mental health and loneliness. Results: Adolescents with NDDs reported elevated levels of adverse mental health across all four waves of data collection. These young people experienced little change in mental health problems and feelings of loneliness over time, and any increase during school lockdowns returned to, or fell below pre‐COVID‐19 levels once schools reopened. In comparison, adolescents without NDDs experienced significant increases from a low baseline in depression symptoms, externalizing symptoms, feelings of isolation, and having a positive attitude to being alone, and evidenced a significant decline in positive mental wellbeing. Quality of friendships were unaffected by COVID‐19 school lockdowns for all adolescents regardless of NDD status. Of the adolescents with NDDs, those with Attention‐Deficit/Hyperactivity Disorder reported a significant increase in positive mental wellbeing following school lockdowns. Conclusions: Adolescents with NDDs emerged relatively unscathed from COVID‐19 school lockdowns and the short term impacts associated with these were not maintained over time. These findings should be considered in the context of this study's geographical location and the unpredictability of school lockdowns. Learning to live with school lockdowns into the future may be a critical element for further investigation in the context of interventions.